Intercultural Sensitivity as a Factor in Perceived Culturally Responsive Teaching of Teachers in Northern Thailand - Charoensilp, Pimmada (rEFLections, 2024)
This study examined the relationship of teachers’ intercultural sensitivity to their in-class culturally responsive teaching. A total of 168 teachers with teaching experience in multicultural classrooms in northern Thailand answered a questionnaire with two psychological scales: the intercultural sensitivity scale and the culturally responsive teaching practice scale. To supplement quantitative findings, 19 teachers from the total number of participants were included in the semi-instructed interview. By conducting factor analysis, intercultural sensitivity perceived by teachers with multicultural facilitation experience in northern Thailand was extracted into three components: interaction engagement, interaction confidence, and respect for cultural differences. The results from structural equation modelling indicate that teachers’ intercultural sensitivity significantly affects teachers’ perceived culturally responsive teaching practices with the largest coefficient size. This study also discussed the associations between teachers’ culturally responsive teaching practices and other significant background factors based on the local context, including school size, non-local student enrolment frequency, overseas travel experience, and the existence of intercultural colleagues.